Diarylethene-containing “stapled” peptides as inhibitors of p53/MDM2 interaction - Bakanovych, I.V.; Strizhak, O.V.; Komarov, I.V.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2020)
Interaction between p53 and the E3 ubiquitin ligase murine double minute 2 homolog (MDM2) is regarded as an important target for anticancer therapeutics. The p53/MDM2 protein-protein interaction is one of the best-studied and most targeted intracellular processes related to cancer progression. Toxicity associated with p53 activation has been reported as a critical issue; therefore, the search for novel selective modulators of this pro tein-protein interaction is of great interest. In this work, the design, synthesis, and study, as the p53/MDM2 interaction inhibitors, of six new “stapled” photocontrolled peptidomimetics — analogues of the known inhibitor pDI — are reported. Photocontrol of peptidomimetic activity was achieved by introducing a photoisomerizable diarylethene fragment into their molecules. Six peptidomimetics bearing the diarylethene group cross-linking amino acid side chains in different positions of the polypeptide strand: (i,i+4), (i,i+7), (i,i+11) were prepared. The stapling was achieved using the Cu-catalyzed “click”-reaction between the diarylethene-based bis-alkynes and two azidoornithine residues placed in appropriate positions of the linear peptide precursors. All the compounds were obtained with the diarylethene moiety in the so-called “open” conformation which can be generated by visible light. They were purified by high performance liquid chromatography. It has been found that the stapling of amino acid residues at positions (i,i+7) in the linear precursor with the diarylethene linker is optimal for obtaining active photocontrolled inhibitors, in terms of the yields of the stapling reaction. Attempts at (i,i+4) and (i,i+11) stapling gave either no product or the compounds, where the diarylethene building block reacted with the peptide precursor through only one alkyne group. The values of the inhibition constants for some of the obtained peptidomimetics measured with the use of a fluorescence polarization assay reached several nanomoles, which puts the obtained peptidomimetics in line with the most active inhibitors of the p53/MDM2 interaction known at the time. Further studies of the obtained compounds as possible candidates for the cancer photopharmacology are warranted.